Spontaneous regression of multiple flow-related aneurysms following treatment of an associated brain arteriovenous malformation: A case report - Andereggen, Lukas; Gruber, Philipp; Anon, Javier; Tortora, Angelo; Steiger, Hans-Jakob; Schubert, Gerrit A.; Marbacher, Serge; Remonda, Luca (Frontiers in Surgery, 2022)
There is no consensus in the treatment strategy of intracranial aneurysms (IAs) associated with brain arteriovenous malformation (BAVM). In particular, it is unknown if a more aggressive approach should be considered in patients harboring a BAVM, in whom multiple aneurysms or a history of aneurysmal subarachnoid hemorrhage (aSAH) is present. We report on an elderly woman harboring multiple aneurysms with a history of SAH due to rupture of an unrelated IA. On evaluation, she was also found to harbor a contralateral, left parietal convexity BAVM. Following resection of the latter, spontaneous regression of two large flow-related aneurysms was encountered. We discuss the therapeutic decision-making, risk stratification, and functional outcome in this patient with regard to the pertinent literature on the risk of hemorrhage in IAs associated with BAVM.